THE CURRENT STATE, DEVELOPMENT TRENDS, AND INVESTMENT DYNAMICS OF SMALL AND MEDIUM-SIZED BUSINESSES IN NAMANGAN REGION (KIUT Publication, 2025)
This article provides a comprehensive analysis of the current state of small and medium-sized enterprises (SMEs) in the Namangan region, the main trends in their economic development, and investment dynamics. The study examines the role of SMEs in the regional economy, their development level across sectors, as well as the results of investment activity in recent years on a scientific basis. The author identifies the factors influencing SME development, existing challenges, and future opportunities, and proposes scientific and practical recommendations for effective management and attraction of investments. The findings of the article have significant scientific and practical importance for improving state policy aimed at supporting SMEs in the Namangan region.